Exergy versus labour in aggregate production functions: estimates for ten large economies. (6th July 2022) - Ayres, Robert U.; Savin, Ivan; Bergh, Jeroen Van Den; Hao, Lu
One can distinguish active (machines) from inactive (infrastructure) capital. Active capital consumes useful energy (or exergy) to do thermodynamic work that muscles and brains usually do. We use data for ten large economies and find that exergy performs just as well as, and hence can replace labour in a Cobb-Douglas production function. This result is robust for each country separately and for all countries estimated together. Furthermore, in estimating a three-factor model (capital, labour and exergy), the coefficients of all three factors are positive and significant when all countries are estimated together. When testing for each country separately the coefficient of exergy, unlike that of labour, is significant for China and Japan, while the opposite holds for the USA and the UK. Our findings underpin the essential role of energy behind GDP growth, and the relevance of exergy as either a substitute or complement for labour in aggregate production functions.